Does Program Evaluation Affect Program Termination? Insights from the Repeal of Corporate Tax Incentives for the Motion Picture Industry. Issue 4 (28th December 2020) - Thom, Michael
Abstract : Policy termination is an understudied phenomenon. The literature identifies some factors that affect its likelihood, but others' importance, especially program evaluation, remain ambiguous. For insight, this study examines the impact of independent program evaluation on the termination of tax incentives for film and television production adopted and then terminated by multiple state governments. Empirical results indicate that termination was significantly more likely after an evaluation showed the incentive's costs exceeded its benefits. Results also indicate a contagion effect. Other factors, including the incentive's age and employment in the entertainment industry, reduced termination likelihood. These findings persisted through several robustness and sensitivity checks. Although critical program evaluation does not guarantee termination, it appears to make it a more likely outcome. Abstract : 关于政策终结的研究并不充足。相关文献识别了影响政策终结可能性的部分因素，但其他因素的重要性，尤其是项目评价，却还很模糊。本文分析了独立项目评价对终结电影电视制作相关的税收激励政策所产生的影响，这些税收激励政策先是被多个州政府采纳，然后被终结。实证结果表明，当项目评价显示激励政策的成本超过收益时，政策终结则更有可能发生。结果还显示存在传染效应。其他因素，包括激励政策在娱乐业的持续时间和使用情况，减少了政策终结的可能性。这些研究发现通过了稳健性检验和灵敏度检验。尽管关键项目评价并不会保证政策终结，但似乎更能导致政策终结。 Abstract : La terminación de la póliza es un fenómeno poco estudiado. La literatura identifica algunos factores que afectan su probabilidad, pero la importancia de otros, especialmente la evaluación de programas, sigue siendo ambigua. Para obtener información, este estudio examina el impacto de la evaluación de programas independientes en la terminación de los incentivos fiscales para la producción de cine y televisión adoptados y luego cancelados por varios gobiernos estatales. Los resultados empíricos indican que la terminación era significativamente más probable después de que una evaluación mostrara que los costos del incentivo excedían sus beneficios. Los resultados también indican un efecto de contagio. Otros factores, incluida la edad del incentivo y el empleo en la industria del entretenimiento, redujeron la probabilidad de terminación. Estos hallazgos persistieron a través de varios controles de robustez y sensibilidad. Aunque la evaluación crítica del programa no garantiza la terminación, parece hacerla un resultado más probable.